2009
DOI: 10.1136/bmj.a3112
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial ultrasound guided or systemic steroid injection for rotator cuff disease: randomised double blind study

Abstract: Objective To compare the effectiveness of ultrasound guided corticosteroid injection in the subacromial bursa with systemic corticosteroid injection in patients with rotator cuff disease.Design Double blind randomised clinical trial.Setting Outpatient clinic of a physical medicine and rehabilitation department in Oslo, Norway.Patients 106 patients with rotator cuff disease lasting at least three months.Interventions Ultrasound guided corticosteroid and lidocaine injection in the subacromial bursa and lidocaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 44 publications
5
95
0
2
Order By: Relevance
“…24 Apart from a benefi cial effect on GTPS, in our patients with comorbidity, the injections might also have had a benefi cial effect on osteoarthritis or low-back pain.…”
Section: Discussionmentioning
confidence: 99%
“…24 Apart from a benefi cial effect on GTPS, in our patients with comorbidity, the injections might also have had a benefi cial effect on osteoarthritis or low-back pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact on therapeutic effect is controversial. A randomised double-blind trial demonstrated evidence that intramuscular steroid is as effective as intrabursal steroid in patients with subacromial impingement [6]. However, both groups in this study received intrabursal lignocaine, which itself may have a therapeutic effect.…”
Section: Image Guidancementioning
confidence: 64%
“…Nevertheless, some have suggested that ultrasound guidance does not make a difference in long-term efficacy [29,30]. The results of one study indicate that local corticosteroid injection with guided ultrasound is no more effective than systemic corticosteroid injection for short-term improvement in rotator cuff disease [31]. Harmon and O'Connor [32] argue that injections may not need accurate ultrasound-guided placement, particularly with corticosteroid, which may diffuse through the tissue planes to affect the target tissue despite inaccuracy.…”
Section: Ultrasound-guided Injectionsmentioning
confidence: 99%